2005
DOI: 10.1300/j385v04n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Gastronomy Tourism

Abstract: The existing literature supports the view that there is a connection between tourism and gastronomy. However, there is little empirical evidence, to show for example, whether or not there is a gastronomy-tourism market segment. Or, does destination's gastronomy contribute to the tourists' quality of experiences while visiting the destination? And, do tourists return to the destination to resample its cuisine?This study was undertaken in Hong Kong which, according to some is a city-destination that offers uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
22

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(97 citation statements)
references
References 7 publications
2
73
0
22
Order By: Relevance
“…For example Rozin (2006), states the gender to be a determinant factor affecting local food consumption when comes to meat avoidance, weight concerns and preference of low-calorie foods among respondents in USA. Kivela & Crotts (2005) supports this idea by pointing that males found to be more interested and involved in local food consumption compared to females. Corroborating with this point, several studies have suggested that females are more concerned about the safety of food, whereas males focus on taste more than safety (Flynn, Slovic, Mertz, 1994;Kim et al, 2009;Wadolowska, Babicz-Zelinska, Czarnocinska, 2008).…”
Section: Demographic Factorssupporting
confidence: 56%
See 1 more Smart Citation
“…For example Rozin (2006), states the gender to be a determinant factor affecting local food consumption when comes to meat avoidance, weight concerns and preference of low-calorie foods among respondents in USA. Kivela & Crotts (2005) supports this idea by pointing that males found to be more interested and involved in local food consumption compared to females. Corroborating with this point, several studies have suggested that females are more concerned about the safety of food, whereas males focus on taste more than safety (Flynn, Slovic, Mertz, 1994;Kim et al, 2009;Wadolowska, Babicz-Zelinska, Czarnocinska, 2008).…”
Section: Demographic Factorssupporting
confidence: 56%
“…For example, Telfer and Wall (2000) reports that tourists; spending on food makes up one-third of total travel expenditure which also reflects the importance of food consumption in tourism. Local food is a major component for both leisure and business segments of tourism industry and eating is the only activity that prompts all five senses; vision, tactile, auditory, taste and olfaction (Kivela & Crotts, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bununla birlikte gastronomi; deniz, kum, güneş turizminden yararlanamayan destinasyonlar için büyük önem teşkil eder (Kivela ve Crotts, 2005). Yerli ve yabancı ziyaretçilere yerel ürünler ve mutfak geleneklerinin sunulması, turist destinasyon imajına yeni bir boyut kazandırır ve destinasyonda ilave ekonomik faaliyetler gelişmesine imkan verir (Halkier, 2012).…”
Section: Yöresel Yemeklerin Destinasyon Pazarlamasına Etkisiunclassified
“…Özellikle destinasyonların ziyaretçilerine sunduğu yerel yemekler destinasyonların turistler tarafından tercih edilmesinde önemli bir rol oynamaya başlamıştır (Dilsiz, 2010: 20). Söz gelimi, Fransa'nın Tuscany ve Lyons bölgelerinin temel turist çekicilik öğeleri olarak yemekleri ön plana çıkmaktadır (Kivela ve Crotts, 2005).…”
Section: Introductionunclassified